Sistem Pakar Diagnosis Diabetes Mellitus Tipe 1 - 2: Forward Chaining - Bayes - Chiuloto, Kalvin; Khairani, Sumi; Hutahuruk, Annisa; Dafitri, Haida (Universitas Multi Data Palembang, 2024)
Diabetes mellitus (DM) is a chronic disease characterized by hyperglycaemia and can lead to serious complications. In North Sumatra, the prevalence of DM reached 5.3%, with 74% of the patients unaware of the condition. The lack of knowledge and restricted access to health care is a challenge in the treatment of DM. The research aims to develop an expert system for early diagnosis of DM types 1 and 2 using the Forward Chaining and Bayes Theorem methods. The system is designed to provide accurate diagnosis and timely information, helping the field community in detecting DM risks early. The implementation of this expert system is expected to raise public awareness of DM symptoms, provide easy access to information, and help in early diagnosis without having to visit a health facility. The use of a combination of Forward Chaining and Bayes methods aims to improve diagnostic accuracy. The system is expected to be an effective tool in the prevention and early treatment of DM in North Sumatra